Pengaruh Kualitas Pelayanan Terhadap Kepuasan Masyarakat Pada Puskesmas Nania Kota Ambon - Selfita Shafyra; Zany I. Aunalal; Laura Nunumete (P3M Politeknik Negeri Ambon, 2024)
Service Quality is a factor that is expected to increase community satisfaction. This study aims to determine the effect of Service Quality on Community Satisfaction at Nania Health Center, Ambon City. The sample was taken from 100 respondents using a non-probability sampling method with a purposive sampling technique. The method used in this research is a simple linear regression analysis method with SPSS 25 software, the regression obtained is Y= 12.189 + 0.669X Based on these results, it can be concluded that Service Quality has a positive and significant effect on Community Satisfaction at the Nania Community Health Center, Ambon City.Keywords: Service Quality and Community Satisfaction